ANALISIS KINERJA KEUANGAN KOPERASI BMT MANDIRI UKUWAH PERSADA BERDASARKAN PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTERIAN KOPERASI DAN UKM RI NO. 07/PER/DEP.6/IV/2016 - LISTIYA MANGGARANI PUTRI, NUR (Jurnal Akuntansi AKUNESA, 2017)
This research’s objective is to analyze financial performance of Baitul Maal wat Tamwil Mandiri Ukhuwah Persada Cooperative in 2012-2016. This research uses quantitative descriptive research using case study method. This research focuss on assesing financial condition aspects, including capital; productive asset quality; efficiency; liquidity; civility and growth.This results show that capital aspect indicates healthy criteria; productive asset quality is not applicable due to unavailability of receivable, financing and asset collectibility data. Moreover, efficiency aspect shows less efficient criteria, liquidity aspect indicates liquid, growth indicates low criteria. The total score of five aspects assesment is 34.5, therefore, the financial performance level of Baitul Maal wat Tamwil Mandiri Ukhuwah Persada is classified as under special supervision. Keywords: capital, efficiency, growth, independence, liquidity, productive asset quality